2010
DOI: 10.1136/bjo.2009.177220
|View full text |Cite
|
Sign up to set email alerts
|

Giant cell arteritis in Asians: a comparative study

Abstract: In our patient population, GCA was seen 20 times less frequently in Asian than Caucasian patients. Although this difference is significantly different (p=0.036), given the small sample size and wide CI this should be viewed as a rough estimate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
1
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(52 citation statements)
references
References 12 publications
0
44
1
4
Order By: Relevance
“…A nationwide survey in 1998 in Japan revealed that the annual incidence rate was 1.47/100,000 people per population aged [50 years, the lowest in the world [6]. This seems due to genetic rather than environmental factors, because GCA occurred less frequently in Asians than in Caucasians [odds ratio (OR) 0.049, 0.0065-0.374, p = 0.03] in the same district in San Francisco [7].…”
Section: Introductionmentioning
confidence: 94%
“…A nationwide survey in 1998 in Japan revealed that the annual incidence rate was 1.47/100,000 people per population aged [50 years, the lowest in the world [6]. This seems due to genetic rather than environmental factors, because GCA occurred less frequently in Asians than in Caucasians [odds ratio (OR) 0.049, 0.0065-0.374, p = 0.03] in the same district in San Francisco [7].…”
Section: Introductionmentioning
confidence: 94%
“…GCA and PMR chiefly affect individuals of white (Caucasian) descent 1. The principal risk factor for both diseases is age.…”
Section: Risk Factors For Gca and Pmrmentioning
confidence: 99%
“…Au Japon, l'incidence annuelle de l'ACG a été estimée à 1,47/ 100 000 [4] et une étude cas-témoin indique que la fréquence de l'ACG est 20 fois moindre chez les sujets asiatiques vivants aux États-Unis comparativement aux sujets nord-américains issus de population blanche [5]. Toujours aux États-Unis, les afro-améri-cains sont 5 à 7 fois moins touchés par l'ACG que les sujets issus de population blanche [5,6]. L'ACG semble aussi très rare dans des populations hispaniques et arabes [5,7,8].…”
Section: Données éPidémiologiquesunclassified
“…Toujours aux États-Unis, les afro-améri-cains sont 5 à 7 fois moins touchés par l'ACG que les sujets issus de population blanche [5,6]. L'ACG semble aussi très rare dans des populations hispaniques et arabes [5,7,8]. L'ACG ne touche que de manière exceptionnelle les sujets avant l'âge de 50 ans et l'incidence la plus élevée est observée chez des personnes de 70 ans et plus [9].…”
Section: Données éPidémiologiquesunclassified